ANALISIS PEMAKAIAN KEBUTUHAN AIR BERSIH DI ASRAMA TOWER 2 SEKOLAH TINGGI PNERBANGAN INDONESIA - Golda Nelce Wonatorei; Suse Lamtiar S; Bachrul Huda (Politeknik Penerbangan Indonesia Curug, 2019)
Based on the existing conditions in the current location, the use of clean water has not reached the standard requirement in the dormitory. Many obstacles faced in the provision of clean water at the peak hour then, the author tries to find a solution to overcome lean of clean water “tower” dormitory. By improving the system of clean water supply properly or installed control system